2019
DOI: 10.1177/0894845319847292
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective and Career Decision-Making Self-Efficacy: A Longitudinal Examination Among Young Adult Students

Abstract: This longitudinal study examined the relationship between Zimbardo time perspectives (TPs) and career decision-making self-efficacy (CDMSE). In total, 1,753 young adults participated in the longitudinal study. For the present study, we selected only participants who were students and provided information on TPs, CDMSE, and sociodemographic characteristics (n ¼ 492, M ¼ 22.97 years, SD ¼ 1.32, 82.9% women). The results of multilevel modeling showed that future orientation and presenthedonistic TPs were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…By the same token, some authors have applied the study of decision-making in adolescents to the vocational sphere, differentiating between males and females (Abidin et al, 2019;Hechtlinger et al, 2019;Kvasková and Almenara, 2019). In these studies, differences were found in the decision-making process variables by gender; the female sample obtained scores better than the male sample.…”
Section: Autonomymentioning
confidence: 99%
“…By the same token, some authors have applied the study of decision-making in adolescents to the vocational sphere, differentiating between males and females (Abidin et al, 2019;Hechtlinger et al, 2019;Kvasková and Almenara, 2019). In these studies, differences were found in the decision-making process variables by gender; the female sample obtained scores better than the male sample.…”
Section: Autonomymentioning
confidence: 99%
“…Individuals high in FTP also tend to believe they are better able to cope with unavoidable negative future consequences and obtain positive future consequences [26], thereby attaining a sense of mastery and control over the pursuit of entrepreneurial opportunities [27]. As a result, individuals with FTP tend to increase their confidence in the transformation of identified opportunities into entrepreneurial career intention [3,13,18,33]. For these reasons, we proposed the following:…”
Section: Mediating Role Of Learning Orientationmentioning
confidence: 99%
“…In particular, future time perspective (FTP), which is defined as "the present anticipation of future goals" [30] (p. 122), can be created by setting motivational goals in the future and by developing long-range behavioral projects to achieve these goals [30]. Research demonstrates that individuals with a deep FTP likely enhance their motivation, learning activity, persistence, and performance [30][31][32][33]. In this study, we thus addressed this gap by investigating if individuals' FTP is associated with their entrepreneurial career intentions and how this link is unfolded.…”
Section: Introductionmentioning
confidence: 99%
“…Future time perspective (FTP) is considered as an important factor that influences individuals' career decisions and long-term development [3]. That is, FTP is predominantly conducted in career decision-making process [4][5][6]. Individuals with high positive expectations for future events choose to set higher goals and will achieve them excellently [7].…”
Section: Introductionmentioning
confidence: 99%
“…Zimbardo and Boyd (2015) [16] (p. 1271) defined time perspective as the "often nonconscious process whereby the continual flows of personal and social experiences are assigned to temporal categories, or timeframes, that help to give order, coherence, and meaning to those events", making time perspective a basic aspect of people's subjective experiences. Past-oriented individuals tend to focus on traditions, family, and history; future-oriented individuals tend to focus on planning, goal setting, and goal attainment [4,25]. Some Author Contributions: I.-J.P. developed research idea/hypotheses, conducted initial data analysis, and wrote the first draft; M.G.…”
mentioning
confidence: 99%